EFEKTIVITAS PENERAPAN TEKNIK CHAINING TERHADAP KEBERHASILAN TOILET TRANING PADA ANAK USIA 2-3 TAHUN DI TPA IHSAN FIKRI KECAMATAN TAMPAN KOTA PEKANBARU - Asfi Yanti We; Ria Novianti; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the observations of toilet training ability in children agedhad 2-3 years are still low because the childs are still using diapers and the techersdidn’t special methods for that. This research aims to determine the effectiveness ofchaining technique implementation for toilet traning ability of children ages 2-3 yearsin TPA Ihsan Fikri Tampan districts Pekanbaru city. The sample of research are 10childrens. The data collection techniques were used that observation. Data wereanalyzed using Wilcoxon test using SPSS 20.0. The hypothesis of research is there is asignificant effect of the application of chaining technique to toilet training childrenaged 2-3 years. It can be seen from the analysis of data obtained by comparing thevalue Wtable = 0 > Warithmetic =8 with an error rate of 5%. It can be concluded that Ho isrejected and Ha accepted which means chaining technique can be used for ability toilettraining in children aged 2-3 years. Application of chaining technique to toilet trainingin children aged 2-3 years in TPA Ihsan Fikri Tampan District Pekanbaru City effect of59,3%.Keywords: Toilet Training, Chaining